Mapping the Field: A Bibliometric Literature Review of Language Attitudes in Sociolinguistic Studies: Pemetaan Bidang: Tinjauan Literatur Bibliometrik tentang Sikap Bahasa dalam Kajian Sosiolinguistik - Angela Carolina Flores Riquelme (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This bibliometric study systematically maps the intellectual structure and evolution of language attitudes research within sociolinguistics using Scopus and Web of Science databases from 2005-2024, employing VOSviewer and Bibliometrix R-package for network analysis, citation mapping, and thematic clustering to reveal significant disciplinary transformation from early sociopsychological frameworks toward critical, intersectional perspectives emphasizing language ideologies, identity construction, and social justice. The analysis demonstrates explosive research growth after 2015, with translanguaging studies achieving exceptional academic impact, particularly Fang and Liu's (2020) research on Chinese university contexts (151 citations, FWCI 15.00), while European institutions, led by Spanish universities, dominate heritage language education research and Asian contexts generate breakthrough empirical studies on multilingual identity construction. Keyword co-occurrence analysis identifies "language ideology," "multilingualism," and "identity" as increasingly central conceptual nodes, reflecting convergence across subfields and movement beyond purely attitudinal measurement toward socio-politically embedded understanding, with the Journal of Multilingual and Multicultural Development emerging as the premier contemporary outlet, experiencing dramatic growth to 8 publications in 2023. However, persistent gaps exist in indigenous languages, sign languages, and non-Western scholarly perspectives, indicating database bias toward English-centric scholarship, revealing distinct research ecosystems where European institutions develop theoretical frameworks while Asian institutions generate high-impact empirical studies. Future research requires addressing geographic imbalances, incorporating underrepresented linguistic contexts, and expanding methodological approaches to achieve more inclusive understanding of language attitudes in global sociolinguistic contexts, demonstrating the field's evolution toward theoretically sophisticated, socio-politically aware scholarship.